QUALITATIVE AND QUANTITATIVE ANALYSIS OF MEDICINAL CHEMICALS OF “ JAMU REMATIK DAN PEGAL LINU “ IN MAGELANG REGION - Haresmita, Perdana Priya; Wardani, Arief Kusuma; Pradani, Missya Putri Kurnia; Permatasari, Lina (Jurnal Ilmu Kesehatan, 2023)
Jamu for rheumatism and "pegal linu" are two of the most commonly used traditional medicine products in the community, so it is a type of traditional medicine preparation that is prone to the addition of medicinal chemicals. Any type of medicinal chemical should not be added to herbal preparations. The purpose of this study was to determine is there any medicinal chemicals in traditional medicine samples for "pegal linu" and rheumatism in the Magelang area. The total number of samples used is nine. Thin layer chromatography was used to analyze medicinal chemicals in traditional medicine, and preliminary organoleptic test was performed. The next step is a quantitative analysis using the UV-Visible spectrophotometric method. Prednisone, mefenamic acid, and ibuprofen were used as standards. The stationary phase was silica gel 60 F254, and the mobile phase was ethyl acetate: chloroform (4:1) for the prednisone standard, chloroform:methanol (9:1) for the mefenamic acid standard, and chloroform:ethanol (8:1) for the ibuprofen standard. Thin layer chromatography analysis showed that three of the nine traditional medicine samples tested positive for prednisone, but none contained mefenamic acid or ibuprofen. Herbs A, D, and E contained prednisone in their samples. Prednisone concentrations in the three samples were 0,252%; 0.754%, and 2,005%, respectively.